Relevance of mast cell infiltration in well-differentiated oral squamous cell carcinoma in biopsy specimen (Mediscope, 2021)
Oral cancer is very common worldwide. More than 90% of all oral cancers are squamous cell carcinoma (SCC). The molecular biological markers of oral SCC have been extensively studied to aid in prevention and prognosis. However, no marker has been universally accepted so far. Mast cells are important component of cancer stromal interaction. Their early recruitment in tumor microenvironment and multifarious function make them a burning topic of interest in the field of research. So mast cell may act as a new target for the adjuvant treatment of oral SCC. Therefore, the aim of the study was to assess the number of mast cell infiltrations in well differentiated oral SCC. In this cross-sectional study the sample size was 66. After routine tissue processing and staining with Hematoxylin & Eosin (H/E) stains slides of all cases were grouped as well differentiated oral SCC. Identification of mast cell was done by Toluidine blue stain. Distribution of mast cells was observed and number of mast cells was counted. The data was tabulated and statistical analysis was performed. The number of mast cell was highly increased in all cases of oral SCC than normal. The mean ± SD number of mast cells was 3.28 ± 1.21 in oral SCC, whereas in control oral tissue it was 0.44 ± 0.19. The p-value was found to be highly significant (p